Perspective Between Central And Regional Government Relations In Legal Problems To Handle Covid-19 Pandemic - Ahmad Sabirin; Febrian Duta Adiyaksa; Raafid Haidar Herfian (Audito Comparative Law Journal (ACLJ), 2022)
The purpose of this article is to describe the perspective between central and regional government relations in legal problems to handling a covid-19 pandemic. The important thing in a constitution is the desire for how the constitutional life of the nation is to be led, which can be seen in the structure and state administration system. There are differences appeared between central and local governments in handling covid-19 pandemic, such as the local lockdown or Pembatasan Sosial Berskala Besar (“PSBB”) policies implemented in several regions in Indonesia, even though Law No. 6 of 2018 concerning health quarantine, the application of PSBB is the central’s government authority. On the other hand, the implementation of PSBB is the responsibility of the regional government to protect society. It seems that the central government’s struggle was preceded by the regional government due to the slow pace of movement that occurred to handle the Covid-19 pandemic the central government. What are solutions to overcoming the legal problems or problems dealing with the Covid-19 pandemic related to the perspective of the relationship between central and regional governments? Normative law research is used as a research method, that conducting by examining library materials as secondary data. The result showed that there is a shared responsibility to handle covid-19 pandemic for both central and regional governments. To make sure that the Joint coordination’s role is done without the friction of authority, it is important to pay attention to the following rules: 1). If the scope of handling covid-19 pandemic is across provinces area. It is the central government’s authority, 2). If the scope of handling covid-19 pandemic is across regencies/cities area. It is the provincial government’s authority, 3). If the scope of handling covid-19 pandemic is in a district/city area, it becomes the district/city government’s authority.